The Attenuation of Pain Behavior and Serum COX-2 Concentration by Curcumin in a Rat Model of Neuropathic Pain - Moini Zanjani, Taraneh (The Korean Pain Society, 2014)
BACKGROUND: Neuropathic pain is generally defined as a chronic pain state resulting from peripheral and/or central nerve injury. There is a lack of effective treatment for neuropathic pain, which may possibly be related to poor understanding of pathological mechanisms at the molecular level. Curcumin, a therapeutic herbal extract, has shown to be effectively capable of reducing chronic pain induced by peripheral administration of inflammatory agents such as formalin. In this study, we aimed to show the effect of curcumin on pain behavior and serum COX-2 level in a Chronic Constriction Injury (CCI) model of neuropathic pain. METHODS: Wistar male rats (150-200 g, n = 8) were divided into three groups: CCI vehicle-treated, sham-operated, and CCI drug-treated group. Curcumin (12.5, 25, 50 mg/kg, IP) was injected 24 h before surgery and continued daily for 7 days post-surgery. Behavioral tests were performed once before and following the days 1, 3, 5, 7 after surgery. The serum COX-2 level was measured on day 7 after the surgery. RESULTS: Curcumin (50 mg/kg) decreased mechanical and cold allodynia (P < 0.001) and produced a decline in serum COX-2 level (P < 0.001). CONCLUSIONS: A considerable decline in pain behavior and serum COX-2 levels was seen in rat following administration of curcumin in CCI model of neuropathic pain. High concentration of Curcumin was able to reduce the chronic neuropathic pain induced by CCI model and the serum level of COX-2.